Isolation and Identification of Antagonistic Bacterium against a Pathogens of Bacterial Tuber Rot of Amorphophallus muelleri - Arfani, Nurfitri; Azrianingsih, Rodiyati; Suharjono, Suharjono (Graduate School, Universitas Brawijaya, 2018)
Rhizosphere bacteria have the ability to protect the host plants from the infection of pathogenic microorganisms. This study aimed to identify rhizosphere bacteria that were capable of inhibiting the growth of bacterial isolates that cause tuber rot of Amorphophallus muelleri. Rhizosphere bacteria were isolated using Nutrient Agar medium by pour plate method. Isolates were subjected to antagonistic assay against several bacterial isolates from the rotten tuber of A. muelleri using dual culture method. The potential isolate was identified based on 16S rDNA sequence. Isolate R7 showed the strongest inhibition to the growth of bacterial isolates from rotten tuber with an inhibition zone diameter of 19.66 mm. The 16S rDNA sequence of isolate R7 R7 was 99.7% similar to Delftia tsuruhatensis PCL1755. The isolate was potential to be developed as phytopathogen control agent.Keywords: Amorphophallus, antagonistic bacteria, rhizosphere bacteria, rotten tuber, 16S rDNA.